The contrast in suspended particle dynamics at surface and near bottom on the river-dominated northern South China Sea shelf in summer: implication on physics and biogeochemistry coupling - Lee, Jay; Liu, James T.; Lin, Yu-Shih; Chen, Chen-Tung Arthur; Wang, Bo-Shian (Frontiers in Marine Science, 2023)
To understand the process-response relations among physical forcing and biogeochemical properties of suspended particles (SPs) in the river-dominated northern South China Sea shelf, a 5-day shipboard observation was conducted at a fixed location on the dispersal pathway of the Zhujiang (Pearl) River plume (ZRP) in the summer of 2016. Instrumented moorings were deployed near the sampling site to record the flow and wave fields every 10 minutes. Hydrographic properties were measured hourly to identify different water masses. Water and SPs samples at the surface (3 m) and near the bottom (3 m above the bed) were taken every 3 h for the analyses of nutrients, chlorophyll-a (Chl-a), and particulate organic matter (POM including POC, PN, and δ13CPOC). Meanwhile, the grain-size composition of SPs and seafloor sediment were also analyzed. Results showed that monsoon winds drove cold upwelling and ZRP waters at the surface. Both the upwelling and ZRP regimes contained newly produced marine phytoplankton based on low POC/Chl-a ratio (PC ratio) and enriched δ13CPOC. However, SPs in the ZRP regime were smaller (<153 µm), having denser particle bulk density, and less enriched δ13CPOC, indicating different bio-communities from the upwelling regime. EOF analysis of the surface data suggested that mixing processes and the dispersal of the ZRP regime were mainly controlled by far-field storm winds, tidal modulation, and strength of mixing. On the other hand, a bottom nepheloid layer (BNL) was observed, mainly consisting of SPs<63 μm with higher bulk density than SPs at the surface. POM in the BNL was degraded and δ13CPOC-depleted according to the PC ratio and δ13CPOC. EOF analysis of the near-bottom data indicated that the dominant physical processes influencing the biogeochemical properties of SPs in the BNL were jointly the upwelling-associated lateral transport (first order) and tide-related resuspension (second order). Our study identified the contrast between the surface and near-bottom regimes with the coupling patterns among physical forcing and physiochemical properties of SPs using good constraints on particle dynamics and particle sources.